2014
DOI: 10.1126/scisignal.2004780
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Osmosensors Hkr1 and Msb2 Activate the Hog1 MAPK Cascade by Different Mechanisms

Abstract: To cope with environmental high osmolarity, the budding yeast Saccharomyces cerevisiae activates the mitogen-activated protein kinase (MAPK) Hog1, which controls an array of osmoadaptive responses. Two independent, but functionally redundant, osmosensing systems involving the transmembrane sensor histidine kinase Sln1 or the tetraspanning membrane protein Sho1 stimulate the Hog1 MAPK cascade. Furthermore, the Sho1 signaling branch itself also involves the two functionally redundant osmosensors Hkr1 and Msb2. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
93
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 47 publications
0
93
0
1
Order By: Relevance
“…We later found that disruption of HKR1 together with MSB2 in the ssk2/ 22⌬ background completely inhibited Hog1 activation, indicating that Hkr1 and Msb2 are functionally redundant (11). Because the signaling mechanisms employed by Hkr1 and Msb2 are significantly different, they were termed the HKR1 and MSB2 subbranches, respectively (12). Msb2, but not Hkr1, also acts at the head of the filamentous growth Kss1 MAPK signaling pathway (15,16).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We later found that disruption of HKR1 together with MSB2 in the ssk2/ 22⌬ background completely inhibited Hog1 activation, indicating that Hkr1 and Msb2 are functionally redundant (11). Because the signaling mechanisms employed by Hkr1 and Msb2 are significantly different, they were termed the HKR1 and MSB2 subbranches, respectively (12). Msb2, but not Hkr1, also acts at the head of the filamentous growth Kss1 MAPK signaling pathway (15,16).…”
mentioning
confidence: 99%
“…The cytoplasmic regions of Msb2 functionally interact with the scaffold protein Bem1 (12). Bem1 binds, among other proteins, Ste20 and its activator, Cdc42.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, disruption of both HKR1 and MSB2 together, in an ssk2/22⌬ background, completely inhibits Hog1 activation, indicating that Hkr1 and Msb2 are functionally redundant (30). Because the signaling mechanisms employed by Hkr1 and Msb2 appear to be significantly different, we have further divided the SHO1 branch into the HKR1 and MSB2 subbranches (29,31). Hkr1 and Msb2 also differentially regulate the filamentous growth Kss1 MAPK signaling pathway (32,33).…”
mentioning
confidence: 99%
“…The cytoplasmic region of Msb2 functionally interacts with the scaffold protein Bem1 (31), which binds, among other proteins, Ste20 and the Ste20-activating protein Cdc42. Thus, Msb2 and Bem1 help activate Ste20 on the plasma membrane.…”
mentioning
confidence: 99%